SISTEM MONITORING KEAMANAN KANDANG SAPI BERBASIS BORLAND DELPHI 7.0 - Annisa, Nur; Danusaputro, Hernowo (JURNAL SAINS DAN MATEMATIKA, 2010)
ABSTRACT--A software for the cow shed security system has been made with Borland Delphi 7.0.This program can observe a cow shed security optimally.The cow shed security monitoring system is done byusing LDR (Light Dependent Resistor) censor. Borland Delphi 7.0 program will display the cow shed securitymonitoring result from a data which sent by a censor. Beside that, this software programming uses BorlandDelphi 7.0 which connecting to Microsoft Access 2007 as a data saving. From this software making which hasbeen done, we had the result that this system can monitoring the cow of shed by LDR (Light Dependent Resistor)censor. Testing result shows that if someone try to enter the cow shed area, automatically LDR (Light DependentResistor) censor will detects and showed software on PC or laptop. Beside that, we will hear the sound of alarmas early warning system.KeyWords: Cow shed, Borland Delphi7.0, database.